2020
DOI: 10.1177/1757975920909119
|View full text |Cite
|
Sign up to set email alerts
|

Use of educational technologies in the promotion of children’s cardiovascular health: a systematic review

Abstract: Objective: The aim of this study was to investigate the effectiveness of educational technologies for cardiovascular health promotion in children. Methods: A systematic review was carried out through a search in Biblioteca Virtual de Saúde, Comissão de Aperfeiçoamento de Pessoal do Nível Superior, EBSCOHot Information Services, and US National Library of Medicine National Institutes of Health databases, using the descriptors: play and plaything, cardiovascular diseases, child, and health promotion, between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In four moderate quality reviews, AVGs were identified as having a positive impact on weight reduction and BMI [30,33,35,37]. On the contrary, two reviews did not find a significant difference between the intervention and control groups in terms of reduction in BMI [30,32], revealing that interventions based on games have a relatively small effect on improving BMI in obese or overweight children [32].…”
Section: Effects On Body Compositionmentioning
confidence: 94%
See 2 more Smart Citations
“…In four moderate quality reviews, AVGs were identified as having a positive impact on weight reduction and BMI [30,33,35,37]. On the contrary, two reviews did not find a significant difference between the intervention and control groups in terms of reduction in BMI [30,32], revealing that interventions based on games have a relatively small effect on improving BMI in obese or overweight children [32].…”
Section: Effects On Body Compositionmentioning
confidence: 94%
“…Seventeen studies were included [18,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], from which 7 were systematic reviews and meta-analysis [18,32,33,36,37,44,45]. All studies focused on children and adolescents of both sexes with an age ranged from 3 to 19 years.…”
Section: Characteristics Of Systematic Reviews or Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation